The spatial-temporal patterns and multiple driving mechanisms of carbon emissions in the process of urbanization: A case study in Zhejiang, China. (15th July 2022) - Zhu, Enyan; Qi, Qiuyu; Chen, Lisu; Wu, Xianhua
Abstract: Urbanization has been viewed as an important factor in rapidly increasing carbon emissions. While urbanization relates to various aspects across space and time, a comprehensive assessment of its influences on carbon emission remains scare. In order to explore the multiple effects of urbanization on carbon emissions, a spatial panel data model was applied in this study, by combing nighttime light remote sensing data form 1995 to 2015 in the case of Zhejiang, China. The results showed that on time series, carbon emissions showed an overall trend of growing rapidly first and slowing down then, and its growth rate was closely related to the socio-economic development. Spatially, high carbon emission areas were mainly concentrated in the northeast and eastern coastal areas, while the southwest regions were the main low-carbon emission areas. Furthermore, the investigation of impact factors revealed that the expansion and fragmentation of urban land, augment of the secondary industry, and consumption behavior would lead to growth in carbon emissions, while the connectivity between urban lands, rising of urban population, and residents' low-carbon awareness could promote carbon mitigation. To be noticed, the impact of economic growth on carbon emissions may gradually be weakening as the industry upgrades. Overall, this research has provided a useful insight into the relationship between urbanization and carbon emissions that can support policy makers and urban planners.